Editorial: Educational Innovations in Countries Around the World: Editorial Comments on the Contributions to a Symposium - Ellis, Arthur K. (International Dialogues on Education Journal, 2019)
This thematic issue of International Dialogues on Education: Past and Present, is dedicated to the topic of educational innovation. The articles contained in these pages focus on innovations in various forms, from pedagogical, to administrative, to technological. The articles are based on presentations made presenters at the 10th Biennial Symposium: Educational Innovations in Countries around the World, held on the campus of Seattle Pacific University, June 24-27, 2019. The symposium featured presenters from 12 countries and three continents.